Perspektif Pendidikan Anak Menurut Syaikh Muhammad Syakir dan Relavansinya dalam Pendidikan Islam Modern di Era Society 5.0 - Mardliyah, Aina'ul (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Education is utilized as a platform to cultivate critical thinking abilities, with the application of technology that impacts religious, national, and governmental aspects of life. This research analyzes the concept of child education, focusing on the perspective of Syaikh Muhammad Syakir and its relevance to modern Islamic education in the era of Society 5.0. Research method: literature review, specifically library research with descriptive analysis. Research findings: (1) The perspective of Syaikh Muhammad Syakir in his work "Kitab Washoya Al Abaa Lil Abnaa" emphasizes moral education, monotheism (tauhid), and proper conduct as essential for shaping a child's character. (2) Modern Islamic education in the era of Society 5.0 centers on the 4C mindset (Critical Thinking, Creativity, Communication, Collaboration) and HOTS (High Order Thinking Skills) for children. (3) The relevance of Syaikh Muhammad Syakir's ideas to modern Islamic education in the Society 5.0 era lies in the interconnectedness of these two educational concepts, resulting in children developing into holistic individuals both personally and socially. The implication is that Syaikh Muhammad Syakir's child education concept potentially provides valuable guidance for modern Islamic education in the Society 5.0 era, focusing on cultivating strong character, moral values, and wise technology utilization.